Study on outage performance gap of two destinations on CR-NOMA network - Hong-Nhu Nguyen; Chi-Bao Le; Nhat-Tien Nguyen; Dinh-Thuan Do (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Non-orthogonal multiple access (NOMA) and cognitive radio (CR) are promising for solving the severe spectral scarcity problem encountered by the next generation of wireless communication systems. This study aims to improve spectral efficiency at two secondary destinations by investigating a CR-NOMA network under situation of the perfect successive interference cancellation (SIC). We also derive the exact outage probability for secondary users. Furthermore, an approximate computation method is applied to indicate more insights. It is confirmed that the performance achieved together with performance gap among two users can be obtained due to different power allocation factors assigned to users.